2011
DOI: 10.1016/s0924-9338(11)73311-9
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary naturalistic study of low-dose ketamine for depression and suicide ideation in the emergency department

Abstract: BackgroundRapid-onset antidepressants could have important clinical impact if their benefits extended to ED patients. We examined preliminary feasibility, tolerability and efficacy of single-dose IV ketamine in depressed ED patients with suicide ideation (SI).MethodsFourteen depressed ED patients with SI received a single IV bolus of ketamine (0.2 mg/kg) over 1–2 minutes. Patients were monitored for 4 hours, then re-contacted daily for 10 days. Treatment response and time to remission were evaluated using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 18 publications
4
45
1
1
Order By: Relevance
“…[12] Furthermore, suicidal cognition was continuously eradicated for 2 weeks in ketamine responders given thrice-weekly, repeat infusions. Similar additional reports in TRD, [13] bipolar disorder, [14] and depressed patients presenting to the emergency department with suicidal ideation [15] suggest that ketamine can reduce suicidal ideation within 40 min of infusion and reductions may be maintained for up to 10 days.…”
Section: Introductionsupporting
confidence: 69%
“…[12] Furthermore, suicidal cognition was continuously eradicated for 2 weeks in ketamine responders given thrice-weekly, repeat infusions. Similar additional reports in TRD, [13] bipolar disorder, [14] and depressed patients presenting to the emergency department with suicidal ideation [15] suggest that ketamine can reduce suicidal ideation within 40 min of infusion and reductions may be maintained for up to 10 days.…”
Section: Introductionsupporting
confidence: 69%
“…None of the studies included in the current meta‐analysis documented major adverse effects, but side effects such as transient headache, dizziness and nausea were commonly reported; such side effects reportedly dissipated fairly quickly, usually once the infusion was complete (aan het Rot et al ., ; Abdallah et al ., ; Thakurta et al ., ; Murrough et al ., ). Many studies also documented the dissociative effects of ketamine in participants (Diazgranados et al ., ; Ibrahim et al ., ; Larkin et al ., ; Zarate et al ., ; Loo et al ., ; Murrough et al ., , ; Carlson et al ., ; Sos et al ., ; Lapidus et al ., ) and increased, if somewhat mild, psychotomimetic experiences (Salvadore et al ., , ; Mathew et al ., ; Larkin et al ., ; Loo et al ., ; Murrough et al ., , ; Sos et al ., ; Lapidus et al ., ). As most studies have not followed the participants beyond 24 h post infusion, any long‐term side effects and addictive potential of ketamine infusion in the treatment of depression are difficult to determine.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 Up to six infusions of repeated ketamine administered once, twice, or three times per week were found to be safe and efficacious in maintaining treatment response. 22,[50][51][52][53] Other studies reported safety and efficacy using a single administration of various routes and doses of ketamine, including 0.2 mg/kg intravenous bolus, 54 50 mg intranasal, 23 and 0.5 mg/kg or 0.25 mg/kg intramuscular injection. 55…”
Section: Safety and Tolerabilitymentioning
confidence: 99%